Association Between Hearing and Vision Impairment and Risk of Dementia: Results of a Case-Control Study Based on Secondary Data - Michalowsky, Bernhard; Hoffmann, Wolfgang; Kostev, Karel (Frontiers in Aging Neuroscience, 2019)
INTRODUCTION: Hearing and vision loss are highly prevalent in older adults and thus very frequently occur in conjunction with cognitive impairments. Studies have shown that hearing impairment is associated with a higher risk of incident dementia. However, evidence concerning the association between vision loss and incident dementia as well as the co-occurrence of vision and hearing loss and incident dementia has been inconclusive. OBJECTIVES: To assess the association between i) either hearing or vision loss and the risk of incident dementia as well as between ii) the combination of both sensory impairments and the risk of dementia. METHODS: This case-control study was based on longitudinal data that included patients aged 65 years and older who had initially been diagnosed with dementia diseases by one of 1,203 general practitioners in Germany between January 2013 and December 2017. In total, n=61,354 identified dementia cases were matched to non-dementia controls, resulting in a sample size of 122,708. Hearing loss and vision loss were identified using documented ICD-10 diagnoses listed in the general practitioners' files. Logistic regression models were fitted to evaluate the associations between visual and/or hearing impairment and the risk of incident dementia, controlled for sociodemographic and clinical variables. RESULTS: Hearing impairment was documented in 11.2% of patients with and in 9.5% of patients without dementia. Any type of vision impairment was documented in 28.4% of patients diagnosed with dementia and 28.8% of controls. Incident dementia was not significantly associated in people with only visual impairment (OR=0.97, CI95% 0.97-1.02, p=0.219), but patients with only hearing impairment were at a significantly higher risk of developing dementia (OR=1.26, CI95% 1.15-1.38, p<0.001), a finding which very likely led to the observed significant association of the combination of visual and hearing impairments and the risk of incident dementia we found in this study (OR=1.14, CI95% 1.04-1.24, p=0.005). DISCUSSION: This analysis adds important evidence to the current paucity of knowledge about the association between hearing and/or vision loss and incident dementia and demonstrates that only hearing impairment affects patients’ cognition and thus may cause an onset of dementia earlier in the affected population.